TINGKAT KEPUASAN MAHASISWA TERHADAP KUALITAS LAYANAN AKADEMIK DAN ADMINISTRASI DI UNIVERSITAS TJUT NYAK DHIEN - Fatmasari, Ayunda; Dwiyanti, Elvyana; Arfansyahh, Zaky (Gapenas Publisher, 2024)
This study aims to analyze the effect of academic service quality and administrative service quality on student satisfaction both partially and simultaneously. This study uses a quantitative associative method. The population in this study were all students of Tjut Nyak Dhien University. The sampling used was students of the Faculty of Economics and Management, Stambuk 2022, Semester 4, Class 03, totaling 51 people. The data collection technique used a questionnaire filling media with a Likert scale, which then the data would be analyzed using the multiple linear regression method with SPSS using the classical assumption test, multiple linear regression, Hypothesis Testing and determination coefficient test. The results of this study indicate that partially the quality of academic service has a significant effect on student satisfaction at Tjut Nyak Dhien University, the quality of administrative service has a significant effect on student satisfaction at Tjut Nyak Dhien University. While simultaneously the quality of academic service and the quality of administrative service have a significant effect on student satisfaction at Tjut Nyak Dhien University